The effectiveness and efficiency of financial realization as the basis for budget projection for 2026–2030 at the regional civil service agency of East Kalimantan province - Maududi, M Tofa; Suharto, Rachmad Budi; Roy, Juliansyah (ARKA INSTITUTE, 2025)
This study examines the effectiveness and efficiency of the budget realization of the Regional Personnel Agency of East Kalimantan Province for the 2020–2024 period, and prepares budget projections for 2026–2030 as a basis for medium-term financial planning. The purpose of this study is to evaluate budget performance and provide recommendations for improvement. The method used is a quantitative descriptive approach with effectiveness and efficiency ratio analysis. Effectiveness is measured by comparing budget realization and targets, while efficiency is calculated from the comparison of budget outputs and inputs. The results show that budget effectiveness tends to be in the effective category, although there are fluctuations that cause some years to be in the moderately effective category. Meanwhile, budget efficiency shows stability in the efficient to very efficient categories. Budget projections for 2026–2030 are prepared by considering historical budget growth and fiscal efficiency policies. These findings are expected to strengthen performance-based budget governance and become the basis for accountable and results-oriented decision-making in local governments. Recommendations include improving budget planning, implementing a periodic monitoring and evaluation system, conducting human resource training, and focusing on program results and impacts to improve the effectiveness and efficiency of the Regional Personnel Agency's budget management.